An introduction to classroom observation - Wragg, E. C. (London ; New York : Routledge, 2012)
How does classroom observation support your professional development? How can you observe as effectively as possible? Highly regarded as one of the most widely used and authoritative texts on this topic, An Introduction to Classroom Observation is an essential text for anyone serious about becoming a good teacher or researcher in education. Now part of the Routledge Education Classic Edition Series, E.C. Wraggs straightforward guide includes a combination of case studies, photographs and illustrations to show how various people study lessons for different purposes and in different contexts. It outlines a range of approaches in clear language and gives examples of successful methods that have been employed by teachers, student teachers, researchers and pupils. With a new preface from Professor Richard Pring, the classic edition of this indispensible text is for a new generation of education professionals serious about becoming good teachers and researchers"--Provided by publisher.
Includes bibliographical references
Keywords: Observation (Educational method); Teachers -- Training of